(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2024)
Ora-pro-nóbis is a non-conventional edible plant recognized for its high protein content, making it relevant in the context of food security and the fight against hunger. The propagation of this plant is mainly carried out through stem cuttings. Therefore, the present study aimed to evaluate vegetative propagation based on the size and physiological maturity of the branches. The experiment was conducted in the municipality of Santo Cristo-RS, using a completely randomized design with 6 treatments and 4 replications, totaling 24 experimental units, each containing 3 cuttings. The treatments consisted of (T1) basal cut of 5 cm, (T2) central cut of 5 cm, (T3) apical cut of 5 cm, (T4) basal cut of 10 cm, (T5) central cut of 10 cm, and (T6) apical cut of 10 cm. The variables evaluated included rooting percentage, number of roots, length of the longest root, root volume, weighted root diameter, root area, fresh root mass, and dry root mass, as well as sprouting percentage, number of sprouts, number of leaves per sprout, fresh mass, and dry mass of the sprouts with leaves. The evaluation occurred 60 days after planting. The results showed differences among the treatments for all analyzed variables. The treatments with basal and central cuttings of 10 cm stood out compared to the treatments with 5 cm cuttings. Treatment 4 was identified as the best option for implementing a production system for this plant, as it presented the best results in characteristics such as the number of leaves, fresh and dry sprout mass, as well as the number of roots and dry root mass.